2022
DOI: 10.1519/jsc.0000000000004376
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Traditional and Rest Redistribution Set Configurations on Explosive-Strength and Strength-Endurance Manifestations

Abstract: Janicijevic, D, Gonz ález-Hern ández, JM, Jim énez-Reyes, P, M árquez, G, and García-Ramos, A. Longitudinal effects of traditional and rest redistribution set configurations on explosive-strength and strength-endurance manifestations. J Strength Cond Res 37(5): 980-986, 2023-This study aimed to compare the long-term effects of resistance training programs based on traditional and rest redistribution set configurations on explosive-strength and strength-endurance performance of lower-body and upper-body muscles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…It is worth noting that RR may perform better in other types of endurance tests. For instance, Janicijevic et al (2022) conducted a muscular endurance test using a two set structure (TS and RR) before and after the intervention for the TS and RR groups, respectively. The participants completed ten repetitions of the bench press or back squat with a load of approximately 75% of 1RM.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that RR may perform better in other types of endurance tests. For instance, Janicijevic et al (2022) conducted a muscular endurance test using a two set structure (TS and RR) before and after the intervention for the TS and RR groups, respectively. The participants completed ten repetitions of the bench press or back squat with a load of approximately 75% of 1RM.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined by Tufano et al (56), “rest redistribution” could be considered a form of time-efficient training. The strategy of rest redistribution is to redistribute overall interset rest time and provide more frequent rest periods (29,56). In their study, Tufano et al (56) implemented rest redistribution methodology by prescribing increased sets, fewer repetitions per set, and brief interset rest periods (approximately 15 seconds).…”
Section: Introductionmentioning
confidence: 99%
“…Further research is suggested with multi-joint movements involving both concentric and eccentric components, and invoking use of the stretch-shortening cycle. More recent research by Janicijevic et al (29) shows promise in the potential of rest redistribution programming to improve lower- and upper-body explosive strength and strength endurance when measured by prescribing exercises for the squat and bench press at 75% 1 repetition maximum (1RM) completed in 30 sets of 1 rep with 31 seconds of interest rest ( p ≤ 0.001; ES = 0.58–3.23). Ultimately, time is not necessarily “saved” with rest redistribution because training time, in theory, remains the same as that for a traditional workout.…”
Section: Introductionmentioning
confidence: 99%